Formation of multifunctional nano-layered oxide REE-containing materials using nitrate precursors - Dryuchko Оleksandr; Storozhenko, Dmytro; Bunyakina, Natalya; Ivanytska, Iryna; Khanyukov, Vasyl; Kytayhora Кateryna (Academic journal Industrial Machine Building Civil Engineering, 2019)
Complex system research of the interaction of structural components in nitrate systems of rare-earth and IA, IIA elements of the periodic system – precursors of modern multicomponent oxide polyfunctional materials on their basis – established the formation of a class of lanthanides alkaline coordination nitrates. The obtained data are the basis for identifying, controlling the formed phases in the preparatory stages of processing in innovative technologies using nitrate predecessors of different electronic structures elements and various combinational methods of their activation, establishing technological and functional dependencies, controlling the modification of the synthesis products properties.